An extreme reason in unwinnable dispute (Anton Chekhov’s “The duel”) - Шелогурова, Галина (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper presents an attempt to interpret the duel in Chekhov’s novella as an argument of the implicit controversy. From this point of view the reason declared by Von Koren (a clash of ideas) is corresponding with plot and seems to be false. The author tries to prove that personal categories (envy, hate) are more significant in the particular type of conflict described by Chekhov.